Factors associated with the oral health-related quality of life in children with intellectual disabilities = Factores asociados con la calidad de vida relacionada con la salud bucal en niños con discapacidad intelectual - Souza Nunes, Filipe de
Different factors can influence the perception of quality of life in individuals with intellectual disabilities. This study investigated the factors associated with quality of life related to oral health in children with intellectual disabilities from the perspective of their parents. A cross-sectional study was carried out with Brazilian children from specialized institutions and their respective guardians. Data were collected through medical records, application of instruments and oral clinical examination (n=92). Most children had poor oral hygiene (64.10%) and a high caries experience (59.8%). The mothers' perception of quality of life related to oral health was low, however there was an association of greater perception when they had low education, female child, less brushing frequency and history of breastfeeding (p≤0.05). Although the perception of quality of life was low, the oral condition found evidences the need to promote oral health education actions with children with intellectual disabilities and their respective guardians.